Contrastive Analysis of Paremiologically Units on The Basis of Professional Lexicon in English and Uzbek Languages (Eurasian Research Bulletin, 2023)
This article analysis of proverb and aphorism are considered as paremiological units, and paremiological units formed on the basis of professional lexicon are cross-analyzed. Differences and similarities in paremiological units of two peoples are demonstrated on the basis of a factual example